THE FORMATION OF DIGITAL COMPETENCE OF STUDENTS OF PROFESSIONAL PRE-HIGHER EDUCATION - BOSKO, Natalia; BELA, Liliia (Physical and Mathematical Education, 2024)
Formulation of the problem. The rapid development of digital technologies, driving production transformation, necessitates skilled professionals with a high level of digital competence. Vocational and higher education institutions must prepare learners for their professional duties, ensuring the acquisition of knowledge, skills, and attitudes forming the basis of digital competence.Materials and methods. The experience of forming digital competence at Kryvyi Rih Professional College of Trade and Hotel and Restaurant Business was analyzed and summarized. The obtained results were systematized using the DigComp 2.2 Digital Competence Framework domains.Results. During the research process, the experience of forming digital competence among Kryvyij Rih Professional College of Trade and Hotel and Restaurant Business learners was generalized and systematized using the domains of DigComp 2.2. It was established that the process commences with "Communication and Collaboration," organizing interaction through messengers, online communication services, and collaborative work. The ICloud platform's effective use requires involvement in the areas of "Information Literacy and Data Literacy" and "Creating Digital Content," additionally utilizing services for gamification, simulators, smartphone sensors, programs, and applications for interactive materials and artificial intelligence tools. Each topic is accompanied by addressing issues of digital security and academic integrity. Developing applicants' competence in "Problem Solving" is one of the most difficult, as it requires a thorough understanding of the professional needs of future professionals and the involvement of appropriate digital tools.Conclusions. The research of experience in the formation of digital competence of applicants of the Kryvyi Rih Professional College of Trade and Hotel and Restaurant Business indicates that the process of classroom and extracurricular work during the study of STEM disciplines provides ample opportunities for it, the involvement of ICT contributes to the formation of a stronger connection between the disciplines studied and the future professional activity of students, that is, is the key to organizing an effective implementation process interdisciplinary relations.
Keywords: digital competence; professional pre-higher education; interdisciplinary connections; ICT; DigComp 2.2.